Tissue Engineering for Rotator Cuff Repair: An Evidence-Based Systematic Review - Maffulli, Nicola (Hindawi Publishing Corporation, 2012)
The purpose of this systematic review was to address the treatment of rotator cuff tears by applying tissue engineering approaches to improve tendon healing, specifically platelet rich plasma (PRP) augmentation, stem cells, and scaffolds. Our systematic search was performed using the combination of the following terms: “rotator cuff”, “shoulder”, “PRP”, “platelet rich plasma”, “stemcells”, “scaffold”, “growth factors”, and “tissue engineering”. No level I or II studies were found on the use of scaffolds and stem cells for rotator cuff repair. Three studies compared rotator cuff repair with or without PRP augmentation. All authors performed arthroscopic rotator cuff repair with different techniques of suture anchor fixation and different PRP augmentation. The three studies found no difference in clinical rating scales and functional outcomes between PRP and control groups. Only one study showed clinical statistically significant difference between the two groups at the 3-month follow up. Any statistically significant difference in the rates of tendon rerupture between the control group and the PRP group was found using the magnetic resonance imaging. The current literature on tissue engineering application for rotator cuff repair is scanty. Comparative studies included in this review suggest that PRP augmented repair of a rotator cuff does not yield improved functional and clinical outcome compared with non-augmented repair at a medium and long-term followup.